1992
DOI: 10.1098/rstb.1992.0032
|View full text |Cite
|
Sign up to set email alerts
|

Litterfall, leaf litter decomposition and litter invertebrates in primary and selectively logged dipterocarp forest in Sabah, Malaysia

Abstract: A two-year study on leaf litter decomposition and litter invertebrates was carried out in a primary (4 ha ( = 4 x 10 4 m 2 )) and logged dipterocarp forest plot (2.5 ha) in the Danum Valley, Sabah, Malaysia. Annual leaf litterfall, leaf litter layer mass and leaf litter decomposition, measured as leaf litter mass loss, were not significantly different between plots. Spatial variation among the 30 replicate sites within each plot was high. Annual rates of total li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(19 citation statements)
references
References 28 publications
1
16
0
2
Order By: Relevance
“…Daily average temperatures vary little throughout the year, with a mean of 26.7°C recorded at the DVFC climate station over the 5-y period, but there is considerable diurnal variation (typically ranging from 22.5°C in the early morning to c. 31°C shortly after noon). The average relative humidity in the open at the DVFC is close to 100% from 18h00 to 08h00 whereas it fluctuates between 60 and 100% during daytime, with annual means of 95% at 08h00 and 72% at 14h00 (Burghouts et al 1992, Marsh & Greer 1992. Characteristics of the forest micro-climate have been given by Brown (1990) and Brown & Whitmore (1992).…”
Section: Climatementioning
confidence: 99%
See 1 more Smart Citation
“…Daily average temperatures vary little throughout the year, with a mean of 26.7°C recorded at the DVFC climate station over the 5-y period, but there is considerable diurnal variation (typically ranging from 22.5°C in the early morning to c. 31°C shortly after noon). The average relative humidity in the open at the DVFC is close to 100% from 18h00 to 08h00 whereas it fluctuates between 60 and 100% during daytime, with annual means of 95% at 08h00 and 72% at 14h00 (Burghouts et al 1992, Marsh & Greer 1992. Characteristics of the forest micro-climate have been given by Brown (1990) and Brown & Whitmore (1992).…”
Section: Climatementioning
confidence: 99%
“…In our previous studies of leaf fall and leaf-litter decomposition in a lowland dipterocarp forest setting in the Ulu Segama Forest Reserve (Sabah, Malaysia), amounts of leaf litter on the forest floor were found to be strongly correlated with local amounts of total leaf fall (Burghouts et al 1992). This suggests that spatial variation in litter turnover may be smaller than expected from variation in litter fall alone.…”
mentioning
confidence: 99%
“…Hal ini sejalan dengan temuan dari MRF, yaitu dengan tidak ditemukannya spesies berencet ini di areal hutan yang ditebang enam tahun yang lalu (O'Brien & Fimbel 2002). Burghouts et al (1992) dan Chung , dalam Hussin & Francis 2001) menemukan bahwa perubahan iklim mikro terkait dengan perubahan penyebaran serta kelimpahan vertebrata yang menjadi sumber makanan berencet. Di lain pihak, Boer (1998) menemukan bahwa terdapat korelasi yang tidak nyata antara kelimpahan serangga, gangguan habitat, dan keragaman serangga sehingga diperlukan penelitian lebih lanjut mengenai hubungan tersebut.…”
Section: Kancilan Berencet Tepusunclassified
“…Tidak ada pola aktivitas yang berbeda secara statistik antara kegiatan di hutan bekas tebangan dan hutan utuh (Colón 1999). Dari invertebrata yang dikenal dimakan oleh musang, hanya Scorpianidae dan Isoptera yang populasinya secara nyata lebih berlimpah di hutan primer, dan Coleoptera dan Hymenoptera lebih umum dijumpai di hutan bekas tebangan (Burghouts et al 1992). Azlan (2003) menemukan bahwa spesies ini adalah karnivora kecil yang paling umum hidup di hutan sekunder berumur 30 tahun di Semenanjung Malaysia.…”
Section: Musang Belang Hemigalus Derbyanusunclassified
“…This agrees with fi ndings from the MRF, where, in an area that had been logged up to six years ago, wren-babblers had yet to return (O'Brien & Fimbel 2002). Burghouts et al (1992) and Chung (1993in Hussin & Francis 2001 found that changes in microclimate were associated with substantial changes in invertebrate distribution and abundance upon which these babblers depend. On the other hand, Boer (1998) found only a low and insignifi cant correlation between insect abundance, habitat disturbance and insect diversity, and further work is needed to explore these relationships.…”
mentioning
confidence: 99%